Wurtzite phase control for self-assisted GaAs nanowires grown by molecular beam epitaxy. (25th January 2021) - Dursap, T; Vettori, M; Botella, C; Regreny, P; Blanchard, N; Gendry, M; Chauvin, N; Bugnet, M; Danescu, A; Penuelas, J
Abstract: The accurate control of the crystal phase in III–V semiconductor nanowires (NWs) is an important milestone for device applications. Although cubic zinc-blende (ZB) GaAs is a well-established material in microelectronics, the controlled growth of hexagonal wurtzite (WZ) GaAs has thus far not been achieved successfully. Specifically, the prospect of growing defect-free and gold catalyst-free wurtzite GaAs would pave the way towards integration on silicon substrate and new device applications. In this article, we present a method to select and maintain the WZ crystal phase in self-assisted NWs by molecular beam epitaxy. By choosing a specific regime where the NW growth process is a self-regulated system, the main experimental parameter to select the ZB or WZ phase is the V/III flux ratio. Using an analytical growth model, we show that the V/III flux ratio can be finely tuned by changing the As flux, thus driving the system toward a stationary regime where the wetting angle of the Ga droplet can be maintained in the range of values allowing the formation of pure WZ phase. The analysis of the in situ reflection high energy electron diffraction evolution, combined with high-resolution scanning transmission electron microscopy (TEM), dark field TEM, and photoluminescence all confirm the control of an extended pure WZ segment, more than a micrometer long, obtained by molecular beam epitaxy growth of self- assisted GaAs NWs with a V/III flux ratio of 4.0. This successful controlled growth of WZ GaAs suggests potential benefits for electronics and opto-electronics applications.